2016
DOI: 10.1002/2015jf003672
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment, motion, and deposition of coarse particles transported by water over a sloping mobile bed

Abstract: International audienceIn gravel bed rivers, bed load transport exhibits considerable variability in time and space. Recently, stochastic bed load transport theories have been developed to address the mechanisms and effects of bed load transport fluctuations. Stochastic models involve parameters such as particle diffusivity, entrainment, and deposition rates. The lack of hard information on how these parameters vary with flow conditions is a clear impediment to their application to real-world scenarios. In this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 111 publications
(237 reference statements)
9
71
0
Order By: Relevance
“…Therefore, the global proportion of motion was estimated by pooling all the observed particles. Using this approach, one envisions each particle observation as a random outcome of the same process, as discussed by Heyman et al (). Therefore, the global proportion of motion was estimated using a new version of equation that jointly considered the contributions of all the observed particles to a global T m and a global T : ϑm0.5emi=1NTAm()ii=1NTA()i …”
Section: Application To Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the global proportion of motion was estimated by pooling all the observed particles. Using this approach, one envisions each particle observation as a random outcome of the same process, as discussed by Heyman et al (). Therefore, the global proportion of motion was estimated using a new version of equation that jointly considered the contributions of all the observed particles to a global T m and a global T : ϑm0.5emi=1NTAm()ii=1NTA()i …”
Section: Application To Experimental Resultsmentioning
confidence: 99%
“…When the area A is not sufficiently large to consider N A as constant, a correlation term must be added to equation . As discussed in Ballio et al (), if one considers an instantaneous solid discharge equal to the product of instantaneous concentration and velocity ( Q / B = Cu ), then the time‐averaged solid discharge is Qtrue¯B=trueC¯0.12emtrueu¯+trueC'u'¯, where the correlation term can be interpreted as a diffusive flux (e.g., Ancey & Heyman, ; Furbish, Roseberry, et al, ; Heyman et al, ). The relative weight of the mean and fluctuating terms in equation may also depend on the choice of the variables.…”
Section: Proportion Of Motionmentioning
confidence: 99%
“…Previous studies have shown that the retention of bed load is hydraulically initiated as soon as the barrier causes a hydraulic jump upstream underlying generally supercritical flow conditions (Schwindt et al, 2017a(Schwindt et al, , 2017b. Supercritical flow conditions are typical in mountain rivers but not omnipresent (e.g., Heyman et al, 2016). This study is limited to supercritical flow conditions, where the Froude number in the non-constricted channel is generally larger than unity.…”
Section: Design Approach For Permeable Sediment Traps 25mentioning
confidence: 99%
“…The lack of hard information on how particle diffusivity, entrainment and deposition rates vary with flow conditions and sediment supply, see Bohorquez and Ancey [55] and Heyman et al [56], is a clear impediment to the application of movable bed models at the expense of increasing uncertainties.…”
Section: Two-dimensional Shallow Water Modelling Computational Mesh mentioning
confidence: 99%